Comparison of SYNTAX Score And Residual SYNTAX Score in Patients Undergoing Multivessel Coronary Intervention - Mumtaz, Zahid; Aslam Khattak, Zahoor; Bilal Siddique, Muhammad; Ali Rizvi, Syed Murtaza; Bilal, Ahmed; Ishaq, Zeeshan (Pakistan Armed Forces Medical Journal, 2024)
Objective: To associate the SYNTAX score, residual SYNTAX score and in-hospital outcomes in patients who underwent multivessel Percutaneous Coronary Intervention.Study Design: Analytical, Cross-sectional Study.Place and Duration of Study: Cardiac Cath Lab, Armed Forces Institute of Cardiology/National Institute of Heart Diseases, Rawalpindi, Pakistan, from Jul to Oct 2023.Methodology: Total three hundred and sixty-six patients who underwent multivessel coronary intervention were included using non-probability consecutive sampling. Patients with history of CABG and complex coronary artery disease were excluded. SYNTAX score and residual SYNTAX score were calculated. Chi-square test and Wilcoxon Signed Rank test were applied to find associations. p